2022
DOI: 10.1017/s000711452200263x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and interpretation of latent class modelling strategies to characterise dietary trajectories across early life: a longitudinal study from the Southampton Women’s Survey

Abstract: There is increasing interest in modelling longitudinal dietary data and classifying individuals into subgroups (latent classes) who follow similar trajectories over time. These trajectories could identify population groups and timepoints amenable to dietary interventions. This paper aimed to provide a comparison and overview of two latent class methods: group-based trajectory modelling (GBTM) and growth mixture modelling (GMM). Data from 2963 mother-child dyads from the longitudinal Southampton Women’s Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In this study, the GBTM was used to fit trajectories to children’s repeated measures of physical indicators. Existing studies have demonstrated that both GBTM and growth mixture modelling are suitable for modeling trajectories [ 56 ], and although both methods have different approaches to longitudinal noble modeling, studies have observed strong agreement on the optimal number of trajectories su and have recommended the use of GBTM because it is less computationally intensive [ 57 ]. The strengths of GBTM for fitting somatic growth indicators have been reported and adopted in a number of studies, primarily because it allows researchers to identify and characterize potential subgroups or categories within populations based on different trajectories [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the GBTM was used to fit trajectories to children’s repeated measures of physical indicators. Existing studies have demonstrated that both GBTM and growth mixture modelling are suitable for modeling trajectories [ 56 ], and although both methods have different approaches to longitudinal noble modeling, studies have observed strong agreement on the optimal number of trajectories su and have recommended the use of GBTM because it is less computationally intensive [ 57 ]. The strengths of GBTM for fitting somatic growth indicators have been reported and adopted in a number of studies, primarily because it allows researchers to identify and characterize potential subgroups or categories within populations based on different trajectories [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that dietary patterns during selected life stages can influence eating practices later in life [ 10 , 11 , 12 , 13 ]. For instance, food preferences early in life set the foundation for food choices and eating habits in later childhood and adulthood [ 14 , 15 , 16 ]. Findings from the Saskatchewan Pediatric Bone Mineral Accrual Study suggest that healthy dietary habits established during childhood and adolescence moderately continue into adulthood [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The group-based trajectory modeling (GBTM) method has been used to explore dietary pattern trajectories since 2014 [ 13 , 14 , 18 , 20 ]. This method uses longitudinal data to account for between-individual variation and describe the continuity of different behaviors of groups of individuals through time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation